Tra accoglienza e sicurezza: schieramenti politici e interventi normativi sull’immigrazione in Italia tra il 1986 e il 2008 - Cavazza, Stefano; Costantini, Emanuela; Scarpellini, Emanuela (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
This article examines how Italian political parties framed and regulated immigration between 1986 and 2008, with a brief look at its 1970s origins. Drawing on parliamentary debates, press sources, and scholarship, it links governing coalitions to policy choices and opposition critiques. Using Zincone and Di Gregorio’s typology—solidarist, functionalist, legalist, identitarian—the analysis traces a shift from labour-centred approaches to a politicized, identity-driven agenda within Italy’s bipolar system. Examining the Foschi, Martelli, Turco-Napolitano, and Bossi-Fini reforms highlights growing securitization and the limits of reactive legislation in the post-Cold War Italian political context.